MIASTENIA GRAVIS AND PREGNANCY: A PURPOSE OF TWO CASES IN THE HOSPITAL SAN BARTOLOME - Villacorta, Alfonso (2015)
Myasthenia gravis (MG) is considered an autoimmune neuromuscular disorder, manifested clinically by weakness and easy fatigability of skeletal muscles, mainly of the face and extremities, and the presence of anti-protein acetylcholine receptor antibodies. Being a disease of low incidence, it is rarer still, I find it associated with pregnancy. In the San Bartolome Hospital, he was monitored and attended two myasthenic mothers in 1984 and 1985 respectively, one primigravida with a history of thymectomy and second multiparous without surgical history. Phases of exacerbation of the disease, which were controlled, achieving both pregnancies culminate in optimal conditions was found.